Manejo hídrico na produção de brotos e mudas de quatro clones de Eucalyptus spp - Mori, Neide Tomita [UNESP] (2010)
The present work had as objective to evaluate the morphological, physiological, and biochemical traits of sprouts and seedlings for four eucalypt clones under different irrigation management. The study was compounded by four experiments, where two of them were on clonal garden (A1 and A2) and two for seedling production on nursery (B1 and B2). In all experiments were studied eucalypt hybrid clones (clone 1: spontaneous hybrid of E. urophylla – clones 144; clone 2: spontaneous hybrid of E. urophylla – clones 224; clone 3: E.grandis x E. camaldulensis - clone 1277, and clone 4: Eucalyptus urophylla x E. grandis - A08). The design of randomized blocks with tree replications was used for all experiments. The Experiment A1 was set up by 3x4 factorial scheme of three water laminas (4, 7, and 10mm) and four clones. The Experiment A2 was similar to A1, with water laminas of 2.5, 4.5, and 6.5 mm. The Experiment B1 for seedling production was set up by 3x2x4 factorial scheme, considering two irrigation laminas (8 and 11 mm) and four clones. The Experiment B2 was set up through 3x2x4 factorial scheme, considering three irrigation laminas (8, 11, and 14mm), two irrigation frequencies (twice and four times per day), and four clones. We evaluated the substrate leached, evapotranspiration, and morphological, physiological, and biochemical traits in clonal garden experiments. Into the seedling production experiments, were evaluated the morphological traits of aerial parts and roots. Into the clonal garden experiments (A1 and A2), the laminas of 4 and 10 mm did not affect the sprout quantity, dry matter, and green color index of seedlings; and the clones showed different performance when under those laminas. The lamina of 2.5 mm is not recommended for uses on clonal garden, because it influenced on sprout production of all clones and presented high peroxidase enzyme ...